PENGARUH PRODUCT KNOWLEDGE DAN PERSEPSI HARGA TERHADAP PROSES KEPUTUSAN PEMBELIAN DENGAN BRAND IMAGE SEBAGAI VARIABEL MODERASI (STUDI PADA KONSUMEN MOBIL WULING DI DEALER WULING SEMARANG) - Novizal, Guntur; Rizal, Alimuddin (Proceeding SENDI_U, 2020)
The phenomenon of the emergence of Wuling in the Indonesian automotive world is interesting,considering that Wuling's early emergence had a pretty heavy task. Poor assessment of motorcyclesand cars made in China makes Wuling penetration into the Indonesian automotive market difficult. Thisstudy aims to determine whether brand image moderates the effect of product knowledge and priceperception on the purchasing decision process. Wuling car consumers in the city of Semarang whobought products in January 2019 to November 2019 as many as 701 consumers became the populationin the study. The number of samples taken was 100 people selected using accidental sampling technique.Multiple regression analysis and Moderated Regression Analysis (MRA) are used as hypothesis testingtools. The results of the study provide information that partially there is an influence of productknowledge, price perception, and brand image on the purchase decision process, with the influence ofthe three variables of 68.3% and the rest is influenced by other variables not examined by 31.74%.Brand image moderates the influence of product knowledge and price perception on the buying decisionprocess.